Teaching efficacy of using Microsoft Teams in virtual school education: Perceptions of teachers and students - Mitra, Gargee; Wadegaonkar, Ashwini (Journal of Education and e-Learning Research, 2025)
The COVID-19 pandemic necessitated an abrupt transition to virtual learning environments. Microsoft Teams (MS Teams) was adopted by many educational institutions to maintain instructional continuity. This study aimed to explore the perceptions of teachers and students regarding the teaching efficacy of MS Teams, focusing on various educational aspects such as interaction, assessment, engagement, and platform usability. The study surveyed 110 teachers and 475 students using structured questionnaires to gather insights into their experiences with MS Teams during the pandemic-induced shift to online education. A multi-dimensional evaluation of knowledge of technology, effective planning for the virtual classroom, and assessment aspects of e-learning was conducted. The ’Online Teaching Efficacy Scale’ (OTES), a five-point rating scale, was used to understand the efficacy of online teaching by teachers. Findings revealed that teachers were adept at using MS Teams for scheduling and task coordination but faced challenges with interactive tools and online assessment methods. Students appreciated multimedia-rich lessons and found the platform user-friendly but missed personal interaction and rated assessments as inadequate. While MS Teams supported virtual learning effectively, its full potential in teaching efficacy especially in engagement, assessment, and feedback remains underutilized, emphasizing the need for targeted teacher training in digital tools to enhance instructional effectiveness in virtual settings.